alpha-Chymotrypsin catalysed oligopeptide synthesis for hair modelling - Martins, Madalena (2019)
Conventional chemical treatments imply the use of harsh chemicals which can cause serious adverse effects on consumers health, hair fibre and environment. In this work was reported for the first time the modelling shape of Asian hair by oligopeptide coating synthesized by a protease. ?-Chymotrypsin from Bovine pancreas catalysed the oligomerization of the tri-peptides, KCL (Lysine-Cysteine-Leucine) ethyl ester and KSL (Lysine-Serine-Leucine) ethyl ester in aqueous media. The synthesis reaction gave rise to oligopeptides with DP?=?6, which were characterized by mass spectra (MALDI-TOF). The in situ synthesis reaction onto the hair surface, under controlled pH (8.59) and temperatures between 25?°C and 55?°C, formed a coating layer inducing changes in the hair shape from straight to curly. Qualitative and quantitative characterization of coated hair was performed by image visualization and by perming efficiency assessment. The developed strategy revealed to be a safer and cleaner alternative to the conventional chemical treatments generally used for hair shape modification. Low cost associated to the catalyst and lower side effects to the hair fibre, health consumer and environment might lead to the development of a cost-effective and sustainable approach in the hair care industry.